Morphological features of non-parenchymal liver cells of full-term stillbirths from HIV-mono-infected mothers - Sherstiuk, Sergey; Panov, Stanislav; Belozorov, Igor; Liadova, Tetiana (Polish Journal of Pathology, 2021)
Fifty-one liver tissue biopsies of full-term stillbirths from HIV-mono-infected mothers were investigated. All morphometric indices of non-parenchymal liver cells were calculated using the Avtandilov microscopic morphometric grid, which consisted of 100 equidistant points. It was inserted into the microscope ocular tube with a total × 200 microscope magnification. The number of points that were found in the corresponding types of non-parenchymal liver cells determined by immunohistochemistry was calculated. In each case, 10 random microscopic areas were selected and then all data were obtained, calculated and presented as percentages. Morphometric indices of non-parenchymal liver cells: Kupffer cells – 28.3±2.9% [control – 21.2 ±2.5], hepatic stellate cells – 14.1 ±1.4% [control – 9.8 ±1.2], LAL (liver-associated lymphocytes): CD4 – 29.2 ±2.2% [control – 43.3 ±4.9], CD8 – 25.3 ±1.9% [control – 23.1 ±1.7], dendritic cells – 3.9 ±0.3% [control – 2.6 ±0.3]. It was established that at the time of the birth of children from HIV-mono-infected mothers the Kupffer cells showed signs of their proliferation and liver-associated CD4 lymphocytes showed signs of their reduction; hepatic stellate cells showed signs of their proliferation and hyperactivation; dendritic liver cells showed signs of their proliferation.